Análise qualitativa da adesão ao tratamento pós-transplante hepático em adultos - Silva, Juliana Dutra De Araujo [UNIFESP] (2019)
Objective: To understand the experience of adherence to treatment after liver transplantation in adults. Method: An exploratory, descriptive, qualitative study with Laurence Bardin's Content Analysis as a reference for organizing and analyzing data collected in semi-structured interviews. Results: We interviewed 18 adult patients with deceased donor liver transplant, followed in a transplant center in São Paulo. The results emerged from two themes: 1) Illness: patients reported the experience of discovering a silent disease, the severe limitations of illness and the transplant acceptance process, the latter being crossed by coping with illness, waiting for the compatible organ at the ideal time, the information that has no way to cure the disease and finally, the acceptance; 2) Life after transplantation: Patients reflected on whether life after transplantation is normal, evaluating what have improved, which aspects of the health are still recovering, what are the limitations, complications and emotional responses in this new phase. They reported the coping strategies used - such as seeking information, support network, spirituality, and gratitude - and conclude that this is a life of care involving healthy living habits, continuous use of medication, and outpatient followup, to which they will respond adhering or not. Going through all these moments of life after transplantation, the fear of death was a central finding of the study associated with treatment adherence. Patients who adhere to health care team guidelines may be mobilized by the fear of dying that persist even after transplantation with the threat of graft loss. Non-adherence to treatment was associated with the absence of fear of death, either by the absence of symptoms that would approach them to this reality or by the denial of their own finitude. Conclusion: Behaviors of adherence or nonadherence to treatment after transplantation were associated with emotional responses to illness and fear of death. Thus, interventions to promote adherence should alert patients about the risks (sometimes silent risks) that remain after transplantation and take care of those who are suffering feeling their life continually under threat.